Impact Of Planting Media And Red Corner Extract On Growth On Lada (Piper Nigrum L.) Stumps Of One Ruas - Sulaminingsih Sulaminingsih; Charlie Novianry Panjaitan; Diki Fajaranto (Utan Kayu Publishing, 2024)
Pepper (Piper nigrum L.) is a valuable spice that is highly profitable, but often difficult to cultivate in the early phase of cuttings growth. This study investigated how different types of growing media and concentrations of extracts from shallots impacted the growth of these single internode pepper cuttings. The study was conducted using a Factorial Randomised Group Design repeated five times. One internode of pepper cuttings was planted on three types of media: soil, soil + compost, soil + burnt husk, and soil + sand. In addition, they were treated with onion extract at concentrations of 200 millilitres of onion extract per litre of water, 250 millilitres of onion extract per litre of water, and 300 millilitres of onion extract per litre of water. Observations included root length, number of leaves, and shoot height. Results showed that the growing medium and concentration of shallot extract greatly affected the growth of pepper cuttings. The mixed media of soil + compost with 300 ml shallot extract/L water produced the best growth for shoot height and number of leaves observed. This proves that soil + compost mixed media with 300 ml/L shallot extract may be a good option for pepper cuttings. This study provides a scientific basis for a more productive and efficient method of pepper cultivation.